(3GdeSJbUi aj CeKGd GdYQHs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3CHheMeO Ydj Hf CSYO TaQhg s)
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CKdL Hg UOhQfG ef HQO Gdjbjf, hcSGg CYWGafG eJ JTQja GdESdGe s
(3BNQgG (B:s
(3YLJ fSGA Hfj RjGO YLI cYLjL fShJfG ZOGI GdCQfH ojhgj hdG jQbY(B: (3jVQH def ojaSoO hdG jUdM s
(3fSNI KGfjIs
(3GdChQGb GdNeS GdChdi ecedI Hbde fSNj MOjK s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs